(untitled) (Analysis in Theory and Applications, 2016)
In the present manuscript, we propose the modification of Jain operators which the generalization of Szász-Mirakyan operators. These new class operators are linear positive operators of discrete type depending on a real parameters. We give theorem of degree of approximation and the Voronovskaya asymptotic formula.